Pelatihan Karyawan Pada CV. Arsana Sentosa - Aniqa Asriah; Syafira Adinda Fauzy; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this industrial visit is to find out about employee training and development at CV. Arsana Sentosa which is an important thing to do for CV. Arsana Sentosa, this visit is very important in a visit or scientific article. relevant past visits serve to organize theory and benefits in training among employees. This article discusses knowledge, skills and attitudes about a Human Resource Management relationship that has a goal in training. The purpose of this article is to develop and find innovative training in the future by carrying out training objectives by means of knowledge, skills and attitudes that are honest and good. Articles from the Visit include: The first three are "Knowledge in training" "Ability in employee training" and "attitude in employee training." The method used in this visit is a descriptive method obtained by the author through observation, interviews and documentation. The results of this industrial visit indicate that the human resource management carried out in developing the CV. Arsana Sentosa is implemented through job training, development and innovative training, employee attitude with honesty and mandatory training that is carried out regularly.